An Empirical Study on Demand and Consumers Perception of Organic Food Products - Pallathadka, Laxmi Kirana; Pallathadka, Harikumar; Manoharmayum, Dolpriya Devi (Integrated Journal for Research in Arts and Humanities, 2022)
The term "organic" comes from the Greek word "Organics." Organic foods are created using natural methods. In ancient times, farmers relied on conventional agriculture and natural manure methods. Later on, to boost output, the green revolution was born. Pesticides and insecticides were introduced during the green revolution. However, the usage of insecticides and pesticides has increased over time, resulting in damaged crops and posing several health risks. Then conventional farming was reintroduced under the banner of "organic." Customers are more and more worried about their health than ever before and environmental sustainability nowadays. Consumers of modern times are prepared to pay a premium for organic food since it is unprocessed, healthy, and fresh. There are two categories of buyers: organic and conventional. The barriers to demand organic food for non-organic buyers include increased prices, a lack of information, and unavailability. Governments and marketers must take the lead in promoting organic farming. A consumer education campaign should be created to educate consumers about the advantages of organic food. Farmers must also be recognized for their organic agricultural practices. For example, Mr. Reddy of Hyderabad was just awarded the Padma Shri. He patented his invention for vitamin D-enhanced cereal grains that are more nutritious. He employed a variety of nutrient-enhancing compositions, including carrot extract, maize flour, and sweet potato extract, which, when applied during irrigation, increase the vitamin D content of plants. Positive attitudes towards organic food may increase demand for organic food.